Alegorías, metáforas y símbolos en el cine sobre la Revolución mexicana - Alvaro Vázquez Mantecón (Caravelle)
This work intends to analyze the way Mexican cinema has built allegoric images of the Mexican Revolution through sequences or key scenes which, far from being a collection of official images, show the complexity of the Mexican filmmakers’ vision of the Revolution. They show the resistance or the dialogue with the concept of State and transform history into something which is alive and helps to catch a glimpse of contemporary worries. The object of this analysis is to present a survey and a reflection about the transformation of the meanings that this event had for contemporary Mexican society.